Fifty cases of late prosthetic valve endocarditis: improvement in prognosis over a 15 year period. Issue 1 (July 1987) - Leport, C; Vilde, J L; Bricaire, F; Cohen, A; Pangon, B; Gaudebout, C; Valere, P E
Abstract : The clinical course, prognostic factors, and management of 50 cases of late prosthetic valve endocarditis, occurring more than two months after valve replacement, were reviewed. Twenty nine cases that presented from 1971 to 1980 were compared with 21 cases that presented from 1981 to 1985. Apart from an appreciable decrease in the frequency of neurological complications between the first period (38%) and the second period (10%) no differences in clinical or bacteriological features were seen. Seventeen (59%) of the 29 cases in the earlier period and four (19%) of the 21 cases in the later period died. The rationale for antimicrobial treatment was similar during both periods. Cardiac surgery was performed in eight of 29 cases between 1971 and 1980 and in 11 of 21 between 1981 and 1985; the mean (SD) time between diagnosis of endocarditis and operation was 28 (19) days and 43 (44) days respectively. Six of the eight cases operated on in the first period died as did two of the 11 operated on in the second period. Twenty seven of the 29 cases presenting between 1971 and 1980 were treated with anticoagulants–either warfarin (15 of 27) or heparin sodium (12 of 27). Sixteen of the 21 cases presenting later were given anticoagulants and 15 of these cases were given heparin sodium. Control of anticoagulation was inadequate in nine of the 27 cases treated with anticoagulants during the first period and in only two of 16 treated during the second period. During the first treatment period neurological complications were more frequent when control of anticoagulation was inadequate.